Gender-based analysis of body dissatisfaction among youths in Singapore: findings from the National Youth Mental Health Study - Samari, Ellaisha; Vaingankar, Janhavi Ajit; Tan, Bernard; Chang, Sherilyn; Tan, Yeow Wee Brian; Archana, S.; Chua, Yi Chian; Tang, Charmaine; Lee, Yi Ping; Chew, Chu Shan Elaine; Davis, Courtney; Verma, Swapna; et al. (Frontiers in Psychiatry, 2025)
IntroductionBody dissatisfaction, often arising from the disparity between the perceived ideal and actual body, is prevalent among young individuals and is linked to various mental health issues. Previous research consistently indicates notable differences in body dissatisfaction between males and females. This study used data from a nationwide study to determine the prevalence of body dissatisfaction among young individuals in Singapore. It also aims to identify associated sociodemographic, health-related, and psychosocial factors using a gender-based approach.MethodsData were obtained from 2600 youths aged 15-35 who participated in the National Youth Mental Health Study. Information on sociodemographic background, body dissatisfaction, childhood trauma, BMI, self-esteem, and social media use was collected. Weighted multiple logistic regressions were performed to identify the sociodemographic variables, as well as other health-related and psychosocial factors associated with body dissatisfaction, stratified by gender.Results20.2% (25.7% females; 14.8% males) reported moderate to marked body shape concerns. Among females, younger ages, Indians (vs. Chinese), those with diploma education (vs. university), those with overweight, those with childhood trauma, and those with greater daily social media usage were more likely to report moderate to marked body shape concerns. Among males, those with primary education and below (vs. university), those with overweight, and those with greater daily social media usage were more likely to report moderate to marked body shape concerns.DiscussionThese results emphasize the importance of creating specific public health programs that consider the different experiences and challenges related to body dissatisfaction based on gender. These programs could help promote body image positivity, increase self-compassion, and encourage critical engagement with social media content.